Multivariate statistical evaluation of bone site and sex as parameters for the Fourier transform infrared spectroscopic study of normal bone. Issue 1 (2010) - Kourkoumelis Kourkoumelis, Nikolaos Nikolaos; Tzaphlidou Tzaphlidou, Margaret Margaret
Abstract : Fourier transform infrared spectroscopy combined with multivariate analysis was performed on a series of bone samples in order to investigate possible differences in the molecular fingerprint based on classification either between different sex and bone sites. Cortical femoral, tibia and ulna samples from five male and five female normal Wistar rats were analysed. PCA analysis classified successfully sex-related spectra since the first three principal components explained 95% of the total variance. This was not the case for bone site-related spectra. In all cases, an important aspect is the ionic exchange of phosphate and carbonate ions.